Pengaruh Daya Tarik, Kepercayaan, dan Keahlian Terhadap Keputusan Pembelian - Akhmad Azhar Khurri; N. Rachma; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2020)
AbstractBy using the brand ambassador Cristiano Ronaldo aims to influence the interests, attitudes,and emotions of consumers. By cooperating with Cristiano Ronaldo as a brand ambassador,he is expected to be able to change the interests of his fans to shop at online shopee shops.This study aims to determine and analyze the influence of attractiveness, trust and expertiseon purchasing decisions.In this study the method of collecting data using the questionnaire method (questionnaire).The type of data used in this study is primary data. The analytical method used in this study ismultiple linear regression. This study uses the results of the questionnaire data distributed tostudents of Unisma who live in the Merjosari area and the samples were taken usingpurposive sampling. The number of samples taken was 70 respondents.The results of this study are that attractiveness and trust do not affect purchasing decisionswhile expertise influences purchasing decisions.Keywords: Attractiveness, Trust, Expertise, purchasing decisions